214 COMPARATIVE EVALUATION OF METALLIC SCREWS IN THE REPAIR OF TIBIAL EMINENCE AVULSION FRACTURES. (1st January 2005) - Lowry, A.; Duncan, D.; Mahar, A.; Oka, R.; Chambers, H.; Gillingham, B.
Abstract : Purpose: Pediatric tibial eminence avulsion fractures occur when immature subchondral bone structurally yields before the anterior cruciate ligament (ACL). Repairs with screw fixation may provide the greatest stability to fracture fragments. The purpose of this study was to evaluate the performance of metal screws for fixation of pediatric tibial eminence avulsion fractures compared to bioabsorbable (polymer) screws. Methods: Data for bioabsorbable screws were compiled from a previous phase of the study.* For comparison, six 16-week old bovine knees were dissected, leaving the ACL intact. Tibial eminence avulsion fractures were created using a curved osteotome. These fractures were repaired by a surgeon using metal screws. The repaired knees were then mounted to a servohydraulic materials testing machine at 30 degrees of flexion. After preconditioning, cyclic tensile loads simulating anterior tibial translation were applied to the tibia (5-150N, 1Hz, 200 cycles) then tested to failure. Displacement (mm) and force (N) were recorded for the duration of testing. Gross mechanical stiffness was determined by taking the rate of deformation over the initial loading. Statistics were compared using a one-way ANOVA. (Table ) Conclusion: Polymer screws have been shown to be difficult to place and prone to breakage. This was reflected in the variable performance of the polymer screws. The primary disadvantage of metal screw fixation is that pediatric patients require implant removal to prevent early physeal arrest. Based upon the data of this study, the metal screws showed less deformation during cyclic testing and more consistent mechanical behavior. Both fixation methods may withstand a maximum force greater than a pediatric ACL would experience during rehabilitation. However, the low initial deformation suggests that the metal screw would better maintain repair integrity.